Rapid detection of Brugia malayi in mosquito vectors using a real-time fluorescence resonance energy transfer PCR and melting curve analysis - Tongjit Thanchomnang (2018)
We developed real-time fluorescence resonance energy transfer (FRET) polymerase chain reaction (PCR) combined with melting curve analysis for detection of Brugia malayi DNA in blood-fed mosquitoes. Real-time FRET PCR is based on a fluorescence melting curve analysis of hybrid formed between amplicons generated from a family of repeated DNA element, 153-bp HhaI repeated sequence, specific to genus Brugia and specific fluorophore-labeled probes. The B. malayi-infected mosquitoes were differentiated from Wuchereria bancrofti-infected and uninfected mosquitoes and from genomic DNA of Dirofilaria immitis- and Plasmodium falciparum-infected human red blood cells and human leukocytes by their melting temperature. Sensitivity and specificity were both 100%. Melting curve analysis produces a rapid, accurate, and sensitive alternative for specific detection of B. malayi in mosquitoes, allows high throughput, and can be performed on small samples. This method has the potential for endemic area mapping or monitoring effect of brugian filariasis mass treatment programs. Copyright © 2008 by The American Society of Tropical Medicine and Hygiene.